Beyond Patriarchal Readings: Reassessing Qiwāmah in Classical Qur’anic ‎Exegesis - Agus Imam Kharomen (Jurnal Ulunnuha, 2026)
Studies on Q.S. al-Nisā’ [4]:34 often conclude that classical Qur’anic exegesis reinforces patriarchal ‎authority by positioning men as superior to women in family leadership. However, this view tends to ‎overlook the diversity of interpretations within the classical tafsir tradition. This article re-examines ‎classical interpretations of the phrase al-rijālu qawwāmūna ‘alā al-nisā’ by identifying progressive ‎perspectives that have received limited scholarly attention. Using qualitative library research and a ‎comparative hermeneutic approach, the study analyzes major classical tafsir works from the fourth to ‎eighth centuries Hijri, including those of al-Ṭabarī, al-Māwardī, al-Rāzī, and Abū Ḥayyān. The findings ‎show that classical tafsir is not a monolithic patriarchal tradition. Rather, it contains diverse ‎understandings of qiwāmah that can be grouped into three progressive models. First, the mas’ūliyyah ‎model emphasizes responsibility and care, portraying the husband as a guardian responsible for family ‎welfare. Second, the niẓām model understands qiwāmah as a functional organizational arrangement rather ‎than a sign of male superiority. Third, the qudrah model links qiwāmah to the capacity to provide ‎protection and effective leadership, allowing role flexibility based on competence rather than biological ‎sex. These interpretations indicate that egalitarian and non-hierarchical views of family relations were ‎already present within parts of the classical exegetical tradition. This study challenges the assumption that ‎classical tafsir uniformly legitimizes patriarchy and highlights the plurality of classical Islamic thought. It ‎also demonstrates the relevance of classical interpretations for developing contextual and gender-sensitive ‎readings of the Qur’an in contemporary Muslim societies.‎